Fabrication and evaluation of a highly durable and reliable chloride monitoring sensor for civil infrastructure. Issue 50 (19th June 2017) - Karthick, Subbiah; Kwon, Seung-Jun; Lee, Han Seung; Muralidharan, Srinivasan; Saraswathy, Velu; Natarajan, Rethinam
Abstract : A solid-state alkaline stable polymer coated Ag/AgCl sensor was fabricated for chloride sensing in concrete structures. Abstract : A solid-state alkaline stable polymer coated Ag/AgCl sensor was fabricated for chloride sensing in concrete structures. The Ag/AgCl sensor was fabricated by sintering the AgCl powder with Ag wire. Polypyrrole (PPy) was prepared by simple chemical synthesis. The unwavering character of the prepared PPy coated Ag/AgCl sensor in saturated KCl solution was exemplified by potentiodynamic polarization studies followed by half-cell potential (HCP). The alkaline stability of the Ag/AgCl and PPy coated Ag/AgCl sensor in synthetic concrete pore solution (SCPS) was characterized by HCP, X-ray diffraction (XRD) and scanning electron microscopic (SEM) studies. The PPy coated chloride sensor was calibrated in saturated KCl, distilled water and SCPS with various concentrations of chloride ions. The results showed a good relationship between the sensitivity of the sensor regarding the potential to the logarithm of chloride activity. Further, it was noticed that the potential value remained stable with increasing immersion time.